2010
DOI: 10.1097/01.ogx.0000371710.47597.7a
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Disturbances in Pregnancy

Abstract: A number of studies have reported associations between sleep disorders and adverse outcomes in both elderly and younger populations, but because few included pregnant women it is unclear whether sleep abnormalities during pregnancy are associated with adverse health consequences. Previous reports on sleep and pregnancy have focused only on specific sleep disturbances such as snoring, and most have studied a very heterogeneous population and included

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
130
5
15

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(156 citation statements)
references
References 0 publications
6
130
5
15
Order By: Relevance
“…Poorer global sleep quality, subjective sleep quality, lower sleep efficiency and sleep disturbances were most prevalent during third trimester. These findings were supported by several studies [9,10], including a report of Chinese pregnant women population [33]. The sleep patterns of most pregnant women changed during pregnancy, which might be the reason [6].…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Poorer global sleep quality, subjective sleep quality, lower sleep efficiency and sleep disturbances were most prevalent during third trimester. These findings were supported by several studies [9,10], including a report of Chinese pregnant women population [33]. The sleep patterns of most pregnant women changed during pregnancy, which might be the reason [6].…”
Section: Discussionsupporting
confidence: 74%
“…As pregnancy proceeds, both the number and duration of sleep disorders increase [6]. Sut et al [9] and Facco et al [10] indicated that the risk of poor sleep quality increased in the second and third trimester when compared with the first trimester. Depression symptom was previously indicated to be associated with sleep disturbances during pregnancy [11].…”
Section: Introductionmentioning
confidence: 99%
“…Three studies collected data in the third trimester [17,20,29], one of which included a follow-up at four weeks postpartum [29]. One study examined the first and third trimesters [19], while another examined the second and third trimesters [23]. Four studies collected data during all three trimesters [21,25,27,28].…”
Section: Prevalence Of Wed/rls During Pregnancymentioning
confidence: 99%
“…Six studies had participants who completed self-administered questionnaires [17][18][19][20][25][26][27], another seven conducted face to face interviews [16, 21-24, 26, 29, 31], and three studies did not specify how data was collected [28,30,31].…”
Section: Prevalence Of Wed/rls During Pregnancymentioning
confidence: 99%
See 1 more Smart Citation